RECASTING CHRISTIAN AND CULTURAL RESOURCES FOR ENVIRONMENT AND SUSTAINABILITY - Odchigue, Randy J C (Asian Horizons, 2012)
This paper seeks to address the contextual experience of the question on environment and sustainability in the Philippine milieu. From there, we will endeavour to self-reflexively examine how Christian discourse can overcome its own embedded presuppositions that may have contributed to the environmental colonization. Finally, we will explore what possible cultural resource within the context that may relate to a re-thinking of a Christian framework for just sustainability.